On IMF debt and capital control: evidence from Malaysia, Thailand, Indonesia, the Philippines and South Korea - Mohamad, A.; Imitiaz, M. S.; Mohd Thas Thaker, Hassanudin *; Anwar, M. N. (Emerald, 2020)
Purpose:This study aims to investigate the effects of capital control and external debts after the 1997 financial crisis. Design/methodology/approach: Using system estimation approach, the authors estimate a panel data-based econometric model for data on Malaysia, Thailand, Indonesia, the Philippines and South Korea from 1990 to 2017. Findings: The authors find that on average, the crisis-hit South East Asian economies choosing external debt perform better in achieving greater economic growth and rebound better compared to economies imposing capital control. Originality/value: This study attempts to answer whether a crisis-hit country should impose capital control or opt for external debt to recuperate from the crisis.